2008
DOI: 10.1128/aac.01280-07
|View full text |Cite
|
Sign up to set email alerts
|

Potential Basis for Amphotericin B Resistance in Aspergillus terreus

Abstract: This study investigated the basis for intrinsic amphotericin B (AMB) resistance in Aspergillus terreus. The ergosterol content, cell wall composition, and lipid peroxidation level had no influence on AMB resistance. The level of catalase production in A. terreus was significantly higher than that in A. fumigatus (P < 0.05). This higher-level production may contribute to AMB resistance in A. terreus since oxidative damage has been implicated in AMB action.Invasive aspergillosis has emerged as a leading cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 22 publications
1
87
0
Order By: Relevance
“…On the other hand, evidence suggests that A. fumigatus amphotericin B resistance is unlikely to emerge during treatment for invasive aspergillosis, as amphotericin B MICs remain similar between isolates recovered from patients before and those recovered (14). It was proposed that the basis for the amphotericin B resistance of A. terreus may be the high level of catalase production compared with that of A. fumigatus, although this remains unconfirmed (63).…”
Section: Aspergillus Fumigatus Drug Resistance: the Polyenesmentioning
confidence: 99%
“…On the other hand, evidence suggests that A. fumigatus amphotericin B resistance is unlikely to emerge during treatment for invasive aspergillosis, as amphotericin B MICs remain similar between isolates recovered from patients before and those recovered (14). It was proposed that the basis for the amphotericin B resistance of A. terreus may be the high level of catalase production compared with that of A. fumigatus, although this remains unconfirmed (63).…”
Section: Aspergillus Fumigatus Drug Resistance: the Polyenesmentioning
confidence: 99%
“…Species-specific diagnosis of A. terreus opportunistic infections is clinically important due to this pathogen's resistance to the primary antifungal therapeutic amphotericin B (13,56,66). To date, the identification of A. terreus infections has challenged the most seasoned clinicians (29).…”
mentioning
confidence: 99%
“…To our knowledge this is the first report of an AmB-resistant strain of A. flavus isolated directly from cave sediment. Resistance to AMB has already been documented for other Aspergillus species obtained from clinical samples (Blum et al, 2008;Van Der Linden et al, 2011;Hadrich et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal AMB-resistance has been related with enzymatic activity against oxidative stress for some fungi (Laniado-Laborín & Cabrales-Vargas, 2009;Mesa-Arango et al, 2014). Blum et al (2008) showed that AMB-resistance in A. terreus was highly related with catalase production. Okamoto et al (2004) showed that oxidative damage induced by superoxide was the main activity of AMB against the yeast C. albicans.…”
Section: Discussionmentioning
confidence: 99%